2001
DOI: 10.1023/a:1013815825500
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Overall, perceptions of support were moderate to high, but there was wide variation in perceptions over time. Men under age 65 reported less support than other groups of patients. Importantly, changes in social support were significant predictors of changes in health-related quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
38
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(44 citation statements)
references
References 20 publications
6
38
0
Order By: Relevance
“…Both optimism and social support have previously been found to be related to better coping post-transplant and higher HRQOL following HSCT [9,[13][14][15] and in other patient groups [16][17][18][19][20][21]. Similarly, in an earlier qualitative study exploring the meaning of HRQOL for HSCT patients [22], seven themes were identified that positively influenced HRQOL, including social support, a positive attitude, and having goals, as identified in this study.…”
Section: Discussionsupporting
confidence: 68%
“…Both optimism and social support have previously been found to be related to better coping post-transplant and higher HRQOL following HSCT [9,[13][14][15] and in other patient groups [16][17][18][19][20][21]. Similarly, in an earlier qualitative study exploring the meaning of HRQOL for HSCT patients [22], seven themes were identified that positively influenced HRQOL, including social support, a positive attitude, and having goals, as identified in this study.…”
Section: Discussionsupporting
confidence: 68%
“…Perceived social support improved regardless of treatment assignment. In a HF observational study by Bennett et al, 53 changes in social support predicted changes in 12-month HRQOL. These findings show that social support can be improved, and improved social support can be related to improvement in HRQOL.…”
Section: Discussionmentioning
confidence: 96%
“…In another study. 17 Changes in social support, but not baseline social support, measured by the MOS-SSS predicted changes in HRQOL measured by another disease-specific instrument. However, in other studies, 22, 44 social support measured by the MOS-SSS was not related to HRQOL measured by a generic instrument.…”
Section: Discussionmentioning
confidence: 96%
“…In previous studies in which the relationship between social support and HRQOL was examined, 17, 27, 28 several instruments were used to measure social support or HRQOL. Social support including emotional/information support, positive social interactions, affectionate support, and tangible social support were related to the physical subscale score of the LHFQ, but not to the emotional subscale score or the SF-36 score.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation